Marriage and canonical process in the digital era (Stato, Chiese e pluralismo confessionale, 2022)
SUMMARY: 1. The Church and the technological revolution - 2. Digital family and "liquid" relationships - 2.1 Internet and social networks: "knowledge" of young couples and marriage celebration - 3. Internet, new technologies and "digital" evidence in the process for matrimonial nullity - 4. Has the time come for the remote canonical process? - 5. Conclusions.ABSTRACT: The article proposes to deepen the role of digital technologies' effects on religious culture and on canonical substantive and procedural matrimonial law. The family is confronted with the digital revolution and the cyberfamily represents a demanding challenge also for the Catholic Church, which has always been committed to fostering solid relationships that unfold along existential projects that allow the opening to generativity and oblativity. Starting from the profiles related to its genesis, passing through the celebration and up to the couple's crisis and the judicial intervention, the family - and the law - has to deal with the new technologies and with the "network". The article explores the relationship between marriage nullity and digital technology with regard to the evidence system of the canonical process and presents a proposal for a "protocol", also considering some experiences emerged in the pandemic period, for the remote execution of the sessions of a canonical process of marriage nullity.